Penyuluhan Tentang Gizi Ibu Menyusui Di Desa Matang Puntong Kecamatan Samudera Kabupaten Aceh Utara - Fitri Wahyuni, Yenni; Rosyita, Rosyita; Mawarni, Serlis; Fitriani, Aida; Friscila, Ika (Pusat Riset dan Inovasi Nasional, 2023)
The fulfillment of balanced nutrition in breastfeeding mothers is very important for parents to understand because considering the age of toddlers is a golden period that will determine the development process in the future. The milk consumed by babies is not enough only in quantity but the quality of breast milk. The purpose of this activity is to increase maternal knowledge about nutrition for breastfeeding mothers. Service activities were carried out at the Matang Puntong Health Center in October 2022. This activity is carried out during the implementation of Posyandu and gathers mothers who breastfeed their babies. The activity begins with exploring first, providing information, gathering breastfeeding mothers, providing counseling, holding discussions and evaluating service activities. Activities have been carried out whose results increase maternal knowledge about breastfeeding maternal nutrition by using poster or brochure media. The hope is that health workers can strive for innovative methods to increase maternal knowledge.